LESSONS FROM PADU WAU MAUMERE: EFFECTIVENESS OF HAPPINESS INTERVENTIONS IN REDUCING DEPRESSION AMONG OLDER ADULTS - Pitriani; Nancy, Maria Nona (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
This study aims to provide happiness intervention services to the elderly who experience mild depression so as to reduce the level of depression and the elderly can live old age with happiness. The implementation of student internship activities carried out on the elderly at the Padu Wau Maumere Elderly Social Welfare Home, Watumilok village, Kangae District, Sikka Regency. The time of implementation of internship activities was carried out for 3 months, starting from September 02 to December 20, 2024. After conducting observations and interviews and distributing scales/measuring tools that are in accordance with the problems found in the field, then the author compiles effective interventions to overcome the problems experienced by the elderly. The author uses happiness intervention because it is considered the most effective to apply to elderly people who are in institutions with depression problems. Happiness intervention using 3 therapies, namely group activity therapy, laughter therapy, and relaxation therapy. The implementation of this intervention activity was carried out in the Hall of the Padu Wau Maumere Elderly Social Welfare Home for three days. The results of this study indicate that the applied happiness intervention is proven to be effective in reducing the level of depression in the elderly at Panti Padu Wau Maumere with the results of the post test showing that some respondents who experience moderate and mild depression have decreased. This is evidenced by data testing using the Wilcoxon test.